PEMANFAATAN ALAT BANTU RUMPON ELEKTRONIK TERHADAP PENINGKATAN HASIL TANGKAPAN PADA ALAT TANGKAP GILL NET DI WILAYAH PESISIR KAB. BULUKUMBA - Rahmat Bin Aburaera Sileh; Danial Danial; Ihsan Ihsan (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
The purpose of this study was to determine the yield and type of catch, the comparison of the number of catches and the efforts to manage electronic FADs on Gill Net fishing gear. This research was conducted in Bulukumba waters from February to March 2017. Data collection was carried out by direct observation of fishermen in Bulukumba waters. The samples used in this study were FADs installed by fishermen in the waters of Bulukumba as many as 20 locations. Based on the research results, fish catches with electronic FADs ranged from 98 to 131 fish per fishing trip with a total catch of 2,324 fish. Meanwhile, the usual FAD catches ranged from 51 to 84 fish per fishing trip with a total catch of 1,313 fish and the highest type of fish was selar, followed by male mackerel, Selar bentong, white Kuwe, Layang, Barracuda, selangat and Mata goyang. The ratio between the catch and the use of electronic FADs was 64%, while the regular FADs were 36%. Considering that FADs are an effective tool in collecting fish, a sustainable management strategy is needed, including by (1) community based management, (2) limiting fishing efforts, (3) stopping the addition of shallow marine FADs. , (4) use of fishing gear with large mesh sizes and (5) prioritize the use of deep sea FADs.